Sustaining Judicial Reform: An Evaluation of the National Action Plan for Judicial Reform 2020–2025 (Indonesian Court and Justice Review, 2025)
Judicial reform in Indonesia has long been a strategic priority to enhance transparency, accountability, and public trust in the justice system. The National Action Plan for Judicial Reform 2020–2025 (Rencana Aksi Nasional Reformasi Peradilan) marks the latest institutional effort to address persistent issues such as corruption, inefficiency, and lack of access to justice. This study evaluates the implementation and effectiveness of the Action Plan, focusing on its core pillars: institutional strengthening, case management reform, integrity-building, and public access. Using a qualitative methodology, including policy analysis, interviews with judicial stakeholders, and reviews of implementation reports, the study finds that while the Plan has brought procedural improvements—such as digitalization and case tracking systems—substantive reform outcomes remain uneven. Key challenges include weak inter-agency coordination, limited political commitment, and a lack of independent oversight. Moreover, external pressures, such as political dynamics and budget constraints, have diluted reform momentum. The novelty of this study lies in its mid-term evaluation of a state-driven reform agenda in a hybrid democratic-legal setting. It argues that sustaining judicial reform requires not only institutional strategies but also civic engagement, judicial leadership, and regulatory coherence. This research contributes to broader regional discussions on justice sector reform in emerging democracies and provides policy recommendations for enhancing the effectiveness and sustainability of reform initiatives in Indonesia.